PENYEBAB TINGGINYA PERNIKAHAN DINI DI KANAGARIAN SUNGAI ABU KECAMATAN HILIRAN GUMANTI KABUPATEN SOLOK - ningsih, Mei nesti four; Dasrizal, Dasrizal; Nefilinda, Nefilinda (STKIP PGRI Sumbar, 2013)
This study aims to determine the causes of the high early marriage in kanagarian sungai abu kecamatan hiliran gumanti can be seen from: 1) low public education in kanagarian sungai abu kecamatan hiliran gumanti 2) low income in Kanagarian sungai abu kecamatan hiliran gumanti 3) accessibility of the existing situation in kanagarian sungai abu 4) the state of the environment in kanagarian sungai abu kecamatan hiliran gumanti. This type of research is that the authors use qualitative research. Data were collected through observation, interviews, documentation. Research informants are a couple who married at an early age in kanagarian sungai abu kecamatan hiliran gumanti.The type of data used are primary data and secondary data. The data analysis technique used is the data reduction, data presentation, drawing conclusions and verification. Test the validity of the data is by using tringlasi sources.Results: The cause of the high early marriage is because many people who have found low education, there are only finished elementary school, junior high, and there is also a high school but never graduated, in terms of income, accessibility, and environment in the kanagarian sungai abu kecamatan hiliran gumanti. Research findings in kanagarian sungai abu kecamatan hiliran gumanti the cause of the high early marriage in kanagarian sungai abu kecamatan hiliran gumanti, for people who have a higher education in order to steer the public about the problems married at an early age in kanagarian sungai abu kecamatan hiliran gumanti, and the parents to pay more attention to children - his son gave guidance and direction so that children - children are not falling prey to it - not a good thing or act which is prohibited by religion.